Hungarian Monitoring, 1 January 1990 . [Magyar rádiófigyelő], 1990. január 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's New Year speech - Premier Vaclav Havel announces broad amnesty in New Year speech, avoids power struggles Domestic Affairs: - Interim president of the republic Mátyás Szűrös's New Year speech - Doina Cornea's Hungarian-language New Year speech - Reports on the Romanian situation Economy: - Independent Smallholders', Agrarian Workers and Civic Party (FKGP) protests against sale of agricultural cooperatives Külpolitika: - Gorbacsov újévi köszöntőjéből - A hatalmi harctól óvott újévi beszédében V. Havel államfő,egyben széleskörű amnesztiát hirdetett ki Belpolitika: - Szűrös Mátyás ideiglenes köztársasági elnök Újévi köszöntője - Doina Cornea asszony magyar nyelvű újévi köszöntője a magyarokhoz - Romániai helyzet-beszámolók Gazdaság: - Az FKGP a tsz-ek kiárusítása ellen tiltakozik